1981
DOI: 10.1111/j.1471-0528.1981.tb01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Central Nervous System in Patients With Ovarian Carcinoma

Abstract: In a survey of 430 patients with ovarian cancer, 4 developed brain deposits; 2 had received cis platin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 2 publications
0
32
0
Order By: Relevance
“…Many patients, regardless of disease stage at presentation or at follow-up, do not routinely undergo brain imaging as part of the metastatic workup, given that some lesions remain asymptomatic. Several authors recently have called attention to the rising incidence of EOC metastatic to the brain [7,8]. Other recent studies have reported that the incidence of brain metastases has increased over time to 2%-4% [21].…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…Many patients, regardless of disease stage at presentation or at follow-up, do not routinely undergo brain imaging as part of the metastatic workup, given that some lesions remain asymptomatic. Several authors recently have called attention to the rising incidence of EOC metastatic to the brain [7,8]. Other recent studies have reported that the incidence of brain metastases has increased over time to 2%-4% [21].…”
Section: Incidencementioning
confidence: 99%
“…The Oncologist ® [7] or that cisplatin-based chemotherapy may contribute to the increased incidence of CNS metastases [21,53,62]. The integrity of the BBB is thought to limit delivery of large hydrophilic drugs to the site of brain metastases, thus presenting problems in choosing which agents and doses to use [53].…”
Section: Brain Metastases In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that almost all patients with EOC receive chemotherapy after initial diagnosis [27]. Some researchers have suggested that the increased incidence of brain metastasis in EOC is related to the effectiveness of chemotherapy [28], or that cisplatin-based chemotherapy may contribute to an increase in the incidence of CNS involvement [29,30], Thus, therapy of brain metastases with combination of surgery, WBRT and chemotherapy, or combination of surgery and WBRT or SRS (stereotactic radiosurgery)/GKRS (gamma-knife radiosurgery) yielded better survival results (median survival of 20, 17, and 18 months, resp.) than therapy of brain metastases with surgery alone, WBRT alone, chemotherapy alone, WBRT and chemotherapy, and no treatment (median survival of 6.7, 4.5, 7.5, 9.1, and 1.4 months, resp.).…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian primaries have accounted for about 1% of patients with brain metastases [I, 2]. Two current reports suggest that the incidence of this problem may be increasing [3,4]. The recent appearance of several such patients at NYU Medical Center prompted this review.…”
Section: Introductionmentioning
confidence: 99%